Key factors of brewery wastewater influencing treatment efficiency and power output of microbial fuel cells - Brunschweiger, Sarah; Kranich, Vera; Haseneder, Roland; Hofmann, Thomas; Glas, Karl (BrewingScience, 2021)
Brewery wastewater treatment with microbial fuel cells (MFC) offers an alternative to conventional biological treatment that could make a wastewater treatment plant profitable even for smaller breweries. The great potential of MFCs lies in their ability to treat wastewater and generate electrical energy simultaneously. However, the efficiency of MFCs strongly depends on the wastewater composition. Therefore, identifying the main factors in brewery wastewater affecting the degradation of organic substances and the power density of MFCs is necessary. For this purpose, identical MFCs were operated with brewery wastewater and diluted beer wort for ⁓180 days. The fermentable sugars in beer wort were first degraded to acetate and the absence of cleaning and disinfecting agents had no influence. However, the high proportion of easily degradable organic acids, influencing the biofilm composition, and higher conductivity of brewery wastewater resulted in an almost twice as high mean degradation rate of 82 ± 8 % and mean power density of 58 ± 24 mW/m3. The change from beer wort to brewery wastewater indicated that the process conditions, not the inoculum, determine the microbial composition of the biofilm. Inhibiting competing methanogens will be mandatory to enhance the energy efficiency needed to become competitive with conventional biological treatment.